Analisis Penggunaan Gadget Terhadap Perkembangan Sosial Anak Usia Dini Di Lingkungan Umbul Tengah - Maesaroh Maesaroh; Mahsiani Mina Laili; Popi Dayurni; Ratu Yustika Rini; Galuh Mulyawan (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
The rapid growth of digital technology has increased gadget use among early childhood, including those living in Umbul Tengah. Excessive screen exposure raises concerns regarding its potential impact on children’s social development, as many children spend more time watching entertainment videos and playing games rather than engaging in direct social interaction. This study aims to describe gadget-use patterns, types of accessed content, and parental strategies to manage gadget dependence among young children. A descriptive qualitative design with a naturalistic approach was employed. Data were collected through in-depth interviews with five parents and observations of five children aged 1–6 years. The findings show that children use gadgets for 1–3 hours daily, exceeding the duration recommended by the American Academy of Pediatrics. The majority of content accessed includes entertainment such as animated videos, children’s songs, and digital games, while educational content is accessed only minimally. Parental strategies identified in this study include limiting screen duration, redirecting children to alternative activities, and providing close supervision during gadget use. However, time-limits alone are often ineffective without consistent rules and engaging alternative activities. Parental mediation plays a crucial role in reducing excessive gadget use and preventing negative impacts on children’s social development